A Smart Monitoring Berbasis Internet of Things (IoT) Suhu dan Kelembaban pada Kandang Ayam Broiler: Smart Monitoring Based on Internet of Things (IoT) Temperature and Humidity in Broiler Chicken Cage - Yogi Isro Mukti; Fitria Rahmadayanti; Diti Tri Utami Diti (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
This study aims to design and build Internet of Things-based smart monitoring of temperature and humidity in broiler chicken coops in Talang Kemiling Pagar Alam that can facilitate and help breeders. This research is monitoring temperature and humidity which still uses the farmer's body itself as a temperature and humidity sensing tool, so that farmers do not know what the actual temperature and humidity are in the chicken coop. Therefore it is necessary to make a tool that can monitor temperature and humidity conditions in broiler chicken coops by utilizing the existing internet network using temperature and humidity sensors, namely DHT11, 1 channel relay for lamp control, and NODEMCU ESP8266 as a microcontroller that processes and transmits data from sensors. to the telegram server via the internet network, the telegram application on an android smartphone is used as an interface for monitoring temperature and humidity in broiler chicken coops remotely. This research uses the Rapid Application Development (RAD) system development method. The stages taken are Requirement Planning, Design Workshop, Build The System and Implementation. To obtain data in this study, researchers conducted data collection techniques including observation, interviews and literature study. The results expected from this study are the tools produced can help and facilitate breeders in raising broiler chickens.